Corona-Generated Space Charge Characteristic in an Indoor HVDC Corona Cage Under Atmospheric Temperature Conditions - Jules Simplice Djeumen; Hendrick Musawenkosi Langa; Trudy Sutherland (Energies)
This study conducted experiments and simulations to examine the DC corona-generated space charge characteristics and understand the performance of high-voltage direct current (HVDC) transmission lines. In experimental studies, various gradient temperatures are tested on a standard model of the potential HVDC transmission line in Southern Africa using an indoor corona cage. Initial tests on the single-line model of aluminium TERN conductors measured the DC corona inception voltages (CIVs) as the ambient temperature increased from 25 °C to 42 °C. A daylight ultraviolet corona camera (CoroCam8) has been used for measurements and visualisation; the measurements record temperatures for positive and negative direct current (DC) voltages. Experimental investigations are supplemented by simulations utilising the finite element method (FEM)-based software COMSOL Multiphysics. Following the creation of 3D models of the corona cage and potential conductor arrangement, the electric field distribution on the surfaces of the conductors was examined. The CIV observations and modelling findings determine the setups’ corona inception electric field strengths. The study effectively integrated experimental data from a corona cage with FEM models to assess DC corona properties across different air temperatures thoroughly. The inception voltage levels of corona are significantly influenced by ambient temperature and the space charge generated by corona. The outcomes of the discussion will inform the design of the proposed HVDC transmission line in Southern Africa.